Penggunaan Media Virtual Reality Sebagai Pengganti Karya Wisata Untuk Siswa Kelas Rendah Di Masa Belajar Dari Rumah - Farah Firdiarahma (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2020)
The Covid-19 pandemic gave recommendations to stay at home and establish policies for learning from home, this resulted in students being unable to go to school to carry out learning activities. Likewise field trips which are part of learning activities are usually carried out by students to go directly into the environment and find their own learning information and require students to leave the house By utilizing technology, we are familiar with virtual reality learning media, based on several virtual reality research that has the potential as an innovative learning medium. for low grade students and can improve student learning outcomes. But can virtual reality replace field trip learning? for low grade students in the home study period. This research was conducted with the hope that it can be useful and provide new insights and knowledge related to the use of virtual reality media as a field trip for low-grade students during their learning from home. With virtual reality, students can still do field trips while still paying attention to the steps in the field trip, namely: the preparation period, the implementation period and the return period. Virtual reality that prevents being effective in increasing student interest and learning outcomes can also replace field trips during the Covid-19 pandemic. So that students do not need to leave the house to do field trips.